Selection of Photocopy Business Branch Locations Using the Cut Off Point, AHP and Topsis Methods - Nugraha, A Fajar; Sabrina, Fira (Journal La Multiapp, 2024)
In order to develop and expand business expansion, the photocopy business owner plans to open a new business branch by renting a shophouse. The choice of location requires careful consideration of several factors because it will affect revenue and business strategy to get maximum profit and have an impact on business continuity. The purpose of this study is to analyze the decision to choose the location of the photocopy business branch with four alternative locations. Location selection was carried out using the Cut Off Point method to determine important criteria to consider, Analytical Hierarchy Process (AHP) was used to weight the selected criteria and Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) as a complement in determining the location selection. The results with a Cut Off Point from five competent business experts, selected 8 criteria from 20 criteria such as rental prices, proximity to consumers, and market opportunities. Weighting criteria with AHP obtained three criteria with the highest weight, namely the price of renting a place, market opportunities, and cleanliness of the place. TOPSIS calculation results obtained preference values of 0.704 (Cipayung), 0.647 (Cakung), 0.477 (Cimanggis), and 0.297 (Ciputat). So, the shophouse in Cipayung was chosen as the best alternative.